2019
DOI: 10.3390/ma12172648
|View full text |Cite
|
Sign up to set email alerts
|

Flammability, Smoke, Mechanical Behaviours and Morphology of Flame Retarded Natural Fibre/Elium® Composite

Abstract: The work involves fabrication of natural fibre/Elium® composites using resin infusion technique. The jute fabrics were treated using phosphorus-carbon based flame retardant (FR) agent, a phosphonate solution and graphene nano-platelet (GnP), followed by resin infusion, to produce FR and graphene-based composites. The properties of these composites were compared with those of the Control (jute fabric/Elium®). As obtained from the cone calorimeter and Fourier transform infrared spectroscopy, the peak heat releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…Recently, research works using graphene incorporated materials suggested a possible emerging solution to the NLFs lower adhesion to polymer matrices [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. This motivated, since 2015, an exponential rise in the number of publications on “natural fiber and composite and graphene” [ 3 ] given by the corresponding (red squares) curve in Figure 1 b.…”
Section: The Birth Of a Novel Class Of Composite Materialsmentioning
confidence: 99%
“…Recently, research works using graphene incorporated materials suggested a possible emerging solution to the NLFs lower adhesion to polymer matrices [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. This motivated, since 2015, an exponential rise in the number of publications on “natural fiber and composite and graphene” [ 3 ] given by the corresponding (red squares) curve in Figure 1 b.…”
Section: The Birth Of a Novel Class Of Composite Materialsmentioning
confidence: 99%
“…It has also been reported in the literature that the poor fiber-matrix adhesion leads to the fiber debonding and fiber pull-out failure modes. 50 Also, the weak fiber-matrix interface of the GFRP was further pronounced after the flexural tests, resulting in fiber pull-out under loading. Very similar results have also been observed previously by other researchers for GFRP composites.…”
Section: Resultsmentioning
confidence: 99%
“…17,[19][20] Hal tersebut dimungkinkan karena zat pengikat (crosslinked agent) pada bahan aditif mengandung komposisi kimia tertentu (seperti: resin melamin) yang membuat serat menjadi kaku. [20][21] Selain itu, senyawa aditif secara prinsip juga berlaku sebagai impuritas sehingga mengubah struktur matrik polimer itu sendiri. 21 Tabel 4.…”
Section: Sifat Termal Serat Tekstil Termodifikasiunclassified
“…[20][21] Selain itu, senyawa aditif secara prinsip juga berlaku sebagai impuritas sehingga mengubah struktur matrik polimer itu sendiri. 21 Tabel 4. Data kekuatan tarik serat referensi dan serat termodifikasi.…”
Section: Sifat Termal Serat Tekstil Termodifikasiunclassified